2012
DOI: 10.1590/s0100-06832012000600021
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregation under different management systems

Abstract: SUMMARY(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 29 publications
9
30
0
3
Order By: Relevance
“…These results confirmed those of Neves et al (2003), Portella et al (2012) and Llanillo et al (2013) and showed that the studied management systems result in soil structure differences. Conventional tillage with one plowing, one or two harrowings (depending on the year and need) and NT promoted important changes in the soil structure between 0 and ±50 cm deep, compared to the soils under native forest and other management systems.…”
Section: Evaluation Of the Soil Morphologysupporting
confidence: 91%
See 3 more Smart Citations
“…These results confirmed those of Neves et al (2003), Portella et al (2012) and Llanillo et al (2013) and showed that the studied management systems result in soil structure differences. Conventional tillage with one plowing, one or two harrowings (depending on the year and need) and NT promoted important changes in the soil structure between 0 and ±50 cm deep, compared to the soils under native forest and other management systems.…”
Section: Evaluation Of the Soil Morphologysupporting
confidence: 91%
“…Structural units: general term used to replace aggregates (0-10 cm) and/or clumps (> 10 cm). result in soil pore loss and changes in infiltration rates, water availability, aeration and root penetration in the soil, which affect crop yields and induce erosion (Araújo et al, 2007;Collares et al, 2006;Tavares Filho et al, 2012;Portella et al, 2012;Llanillo et al, 2013).…”
Section: Evaluation Of the Soil Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Materechera et al (1992) also observed a lower proportion of large aggregates in agricultural clay soils cultivated with Lolium multiflorum compared to Triticum spp and Pisum sativum, attributing this result to the greater root length of Lolium multiflorum. The root system of grasses can lead to the change of more compact aggregates into less compact aggregates (Portella et al, 2012) by breaking the aggregates and then reshaping them (Terpstra, 1990) or by stresses generated in the soil-root interface during water extraction, which cause cracks in the soil (Ball et al, 2005).…”
Section: Resultsmentioning
confidence: 99%